Antimicrobial resistance in a protracted war setting: a review of the literature from Palestine - Ramya Kumar; Osama Tanous; David Mills; Bram Wispelwey; Yara Asi; Weeam Hammoudeh; Omar Dewachi (mSystems)
ABSTRACT Antimicrobial resistance (AMR) is an escalating global health crisis. In war-affected regions, where healthcare systems are already compromised, AMR presents an even greater threat. The occupied Palestinian territories (oPt), subjected to chronic war-like conditions, have experienced extensive fragmentation, de-development, and destruction of healthcare. This review maps the existing knowledge regarding AMR carriage and infection in the oPt. We conducted a scoping review using PubMed, CINAHL, Embase, and Web of Science. Findings on the prevalence and suggested drivers of AMR were extracted and analyzed according to the One Health approach. From an initial 1,787 articles, 102 were included in the final analysis. Of these, 91 studies focused on AMR in humans, seven on animals, and four on water contamination. The findings reveal high rates of AMR, with 40% of Klebsiella pneumoniae producing extended-spectrum beta-lactamase (ESBL) and 55% of Streptococcus pneumoniae resistant to penicillin. Additionally, 45.6% of Staphylococcus aureus isolates from cow milk were methicillin-resistant, and 36% of chicken samples contained carbapenem-resistant gram negative bacteria. Significant gaps in the regulation of antibiotic prescription, dispensation, and consumption were reported. Despite the heterogeneity in reporting methods across studies and the inability to perform a meta-analysis, the evidence suggests alarmingly high AMR rates within the oPt. Notably, most studies attributed AMR to local practices, often overlooking broader structural and socio-political drivers. This review underscores the need to contextualize AMR within the environment, particularly under conditions of sustained warfare.IMPORTANCEThis study goes beyond merely reviewing and summarizing data on AMR in the occupied Palestinian territories (oPt), a region enduring chronic war-like conditions. Our work addresses critical gaps in knowledge about AMR in populations affected by war and siege. By contextualizing AMR through a socio-political lens, this study offers a novel perspective. It highlights deeper drivers, including the impact of war on the behaviors and education of patients and doctors, perceptions of antibiotics, the role of humanitarian interventions in fostering antibiotic anarchy, and the overall weakening of the Palestinian healthcare system. Importantly, this review also sets the stage for understanding the existing literature on AMR in the oPt within the context of the ongoing war in Gaza, emphasizing the immediate need for comprehensive strategies to address AMR under conditions of conflict. The insights can inform physicians and policymakers in designing and implementing effective AMR stewardship programs, not only in Palestine but also in other conflict-affected regions.